PENGARUH KEMAMPUAN INTELEKTUAL DAN ETOS KERJA TERHADAP KINERJA PEGAWAI PADA PT BPRS AMANAH BANGSA PEMATANGSIANTAR - Sepri Malik Saragih; Darwin Lie; Marisi Butarbutar; Julyanthry Julyanthry (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2018)
The results of this study can be summed summarized as follows: 1. Intellectual Ability is high, ethic of work is high enough and employee performance is high. 2. Regression analysis result is Ŷ = 33,312 + 0,306X1 + 0,302X2, meaning there is positive influence between intellectual ability and ethic of work on employee performance. 3. The results of the analysis correlations is r = 0,660 which means there is a moderately high and positive correlation between intellectual ability and ethic of work with employee performance. The level of employee performance can be explained 43,6% by intellectual ability and ethic of work. 4. Hypothesis test result stated that H0 is rejected, it means intellectual ability and ethic of work have positive and significant influence on employee performance at PT BPRS Amanah Bangsa Pematangsiantar simultaneously and partially. The suggestions of this research is: 1. To strengthen the intellectual ability, the agency should provide opportunities for further education. 2. To improve ethic of work, employee should try to be more sincere and grateful in working for improving the quality of work. 3. To improve performance, the agency should give opportunity for employees to innovate in order to rise the creativity of work. Keywords: Intellectual Ability, Ethic of Work and Employee Performance.